Golden August: Breastfeeding, a golden act in primary care (International Seven Journal of Multidisciplinary, 2024)
Primary Health Care's essential attributes are first-contact care, longitudinality, comprehensiveness and coordination, with the derived attributes being: family and community guidance and cultural competence. In addition to all the attributes that primary health care has, one of its roles is to encourage the practice of breastfeeding. Their objective is to describe the importance of educational actions about breastfeeding in basic health units. The methodological approach adopted was a descriptive study, which consisted of a report on the experience of nursing students during the practice of Primary Health Care Assistance II, a process of experiences and critical reflections about golden August and breastfeeding, experienced in the 10th period of the Nursing course, in August 2023. It was observed that the activities were carried out in the collective activities room at the UBS where six pregnant women were present. Some in their first pregnancy, and others with experience of a second pregnancy, which contributed to the construction of a dialogue and the teaching-learning process.It was noticeable that there was a construction throughout the action, with interactions between them and the academics in the conversation circle, thus resolving doubts and sharing knowledge. It was presented through the synthetic breast, the anatomophysiological region, exposing the correct region in which the baby should suck, being the areolar region and not the nipple. The signs of correct latch-on were also presented and demonstrated, such as: the positioning of the baby's chin when touching the mother, causing the lips to be directed outwards like a fish's mouth and the flow occurs gradually and without pain. It has been verified that the team's interaction with these women contributes to improving the practice of breastfeeding and facilitating its acceptance and continuity. Based on the above, carrying out health education actions aimed at breastfeeding is essential within the APS. It is clear that exclusive breastfeeding until six months is extremely important for both the baby and the mother. In addition to reducing mortality, it reduces the incidence and severity of some comorbidities. In this way, the experiences enabled the enrichment of knowledge in the professional training of academics, enabling the visualization of new ways of approaching pregnant women, offering comprehensive assistance, and demonstrating the potential of Primary Care in the territory, in families and in the community.